Public spaces and aging: an analysis of the permanence and circulation of elderly people on the Pedestrian Street of Londrina-PR - Bernardes, Sofia dos Santos; Pompermayer , Karine; Mensato , Amanda Zanato; Kanashiro, Milena (Technical and Scientific Journal Green Cities, 2025)
Objective – This study aims to understand how elements of the urban structure support behaviors associated with the subjective well-being of the elderly population. Methodology – Based on behavioral cartographies combining the Static Snapshots and Movement Traces techniques, the behaviors of older adults were recorded along the five blocks of the Calçadão (Pedestrian Street) in Londrina-PR. Non-participant observations were carried out in different shifts (morning, afternoon, and evening) and on three weekdays (Tuesday, Thursday, and Saturday). Originality/Relevance – Given the demographic trend of population aging, the research reinforces the need to rethink urban space as support for the daily lives of a population more vulnerable to health and mobility issues. Understanding how urban configuration relates to the well-being of older adults provides input for interventions aimed at autonomy, safety, and social interaction. Results – The cartographies revealed a consistent sociability pattern: clusters of permanence in attractive points (such as fountains and planters) and in resting areas composed of benches or shaded steps. Headcounts indicated that the presence of older adults was more significant in the afternoon during weekdays, while on Saturdays it was predominantly concentrated in the morning. Theoretical/Methodological Contributions – The research expands the debate on how the built environment influences sociability, permanence, and, consequently, the well-being of older adults. The use of cartographies with a qualitative approach reinforces the importance of capturing social practices in the field and proves effective in identifying patterns of circulation, permanence, and sociability. Social and Environmental Contributions – The study encourages more inclusive and participatory urban policies. It demonstrates how micro-scale elements can contribute to the construction of social meanings in public space and reinforces the importance of accessible and welcoming environments for promoting active aging, which is essential for building healthier and more sustainable cities.